Development and Experimental Research of the Chain Transmission Motion Characteristic Test Rig - Li Yongjian; Lu Tianwei; Wu Luming; Mei Songwei (Jixie chuandong)
The overall design,measurement and control system of chain transmission test rig are described.A lot of experimental test is finished by the developed test rig.The experimental results show that chain transmission speed fluctuation curve and the unevenness coefficient curve is acquired by the test rig comply with the variation laws on the theoretical calculation.Also the high-precision and reliability is verified through the results.The analysis of experimental results has important guiding signification in practical engineering applications of transmission.